2016
DOI: 10.3389/fonc.2016.00247
|View full text |Cite
|
Sign up to set email alerts
|

Functional Significance of Aurora Kinases–p53 Protein Family Interactions in Cancer

Abstract: Aurora kinases play critical roles in regulating spindle assembly, chromosome segregation, and cytokinesis to ensure faithful segregation of chromosomes during mitotic cell division cycle. Molecular and cell biological studies have revealed that Aurora kinases, at physiological levels, orchestrate complex sequential cellular processes at distinct subcellular locations through functional interactions with its various substrates. Aberrant expression of Aurora kinases, on the other hand, cause defects in mitotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 95 publications
3
41
1
Order By: Relevance
“…Several studies have shown that the mitotic Aurora kinase A is a poor prognostic marker in breast cancer [9][10][11]17,18,20], and we found borderline significance for reduced OS in this group of breast cancer patients with early breast cancer treated with adjuvant endocrine therapy. Aurora A is not only a cell cycle regulator but is also involved in many different signaling cross-talks within the cells [5][6][7], including activation of the ER via phosphorylation [12]. Our finding in this study which included 980 early breast cancer patients showed that Aurora A did not show significance as prognostic or predictive marker for response to tamoxifen or to letrozole.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Several studies have shown that the mitotic Aurora kinase A is a poor prognostic marker in breast cancer [9][10][11]17,18,20], and we found borderline significance for reduced OS in this group of breast cancer patients with early breast cancer treated with adjuvant endocrine therapy. Aurora A is not only a cell cycle regulator but is also involved in many different signaling cross-talks within the cells [5][6][7], including activation of the ER via phosphorylation [12]. Our finding in this study which included 980 early breast cancer patients showed that Aurora A did not show significance as prognostic or predictive marker for response to tamoxifen or to letrozole.…”
Section: Discussioncontrasting
confidence: 52%
“…Studies of cell culture models mimicking ER positive breast cancer resistant to the antiestrogens tamoxifen and fulvestrant and also to aromatase inhibitors have disclosed that Aurora kinases are important for growth of both antiestrogen and aromatase inhibitor resistant breast cancer cells [2][3][4]. Aurora kinases (A, B and C) are key regulators of mitosis and multiple signaling pathways [5,6]. Gene amplification and protein overexpression of Aurora kinases have been found in both hematologic malignancies and solid tumors and deregulation of Aurora kinases has been linked to tumorigenesis [7].…”
Section: Introductionmentioning
confidence: 99%
“…The Aurora kinase family, and in particular Aurora A, is required for multiple mitotic events and its aberrant expression is related to tumorigenesis. 22 To date, a number of inhibitors targeting Aurora A, B and pan-Aurora kinase have been approved by the FDA for cancer management, such as for ovarian cancer and acute myelogenous leukemia (AML). 23 Another commonly down-regulated gene is HMMR (Hyaluronan-mediated motility receptor), also known as the receptor for hyaluronan-mediated motility (RHAMM).…”
Section: Resultsmentioning
confidence: 99%
“… 47 AURKA contributes to tumorigenesis through interactions with P53 and Myc. 48 50 Recently, Otto et al 14 showed that Aurora A and N-Myc acted as oncogenic partners in neuroblastomas. AURKA forms a complex with N-Myc, which protects N-Myc from FBW7-mediated proteasomal degradation.…”
Section: Targeting Myc Stabilitymentioning
confidence: 99%